Praktikalitas Sistem Informasi Penerimaan Siswa Baru (PSB) Berbasis WEB (Studi Kasus SMK Negeri 7 Padang) - Yuliawati Yunus; Indah Rahmatika Sari (Jurnal KomtekInfo, 2018)
This research and development is motivated by the problem of registering new students conducted manually so that, it is less effective and there are also many students who come from areas outside the city of Padang. This study aims to determine the Practicality of Designing and Making Information Systems for New Student Admissions Based on Mobile Web of SMK Negeri 7 Padang. This research uses a 4D Research & Development method. The subjects of the study amounted to 21 people, with the design and development steps as follows. (1) Define, in the define step an analysis of the requirements of the system will be carried out (2) Design, in this step a design will be made for the system to be created ( 3) Develop, in this step an assessment phase of the system will be made and (4) Disseminate, at this stage the product distribution has been made. Practicality testing is carried out on the Information System for New Student Admissions Based on the Valid Mobile of SMK Negeri 7 Padang. The overall practicality assessment results of the practical assessment of the New Student Admissions Information System Based on SMK Negeri 7 Padang Mobile Web is 86.26%, so the practical level can be interpreted to be very practical to use. In conclusion, based on the assessment along with expert input as well as the results of the field trial of the New Student Admissions Information System Based on Mobile Web as an information system that has been tested for its feasibility, excellence, and can be used in the admission process of SMK Negeri 7 Padang